PTSD, dysregulation profile and substance use: exploring differences in a sample of adolescents in an outpatient clinic - Reyentanz, Emely; Basedow, Lukas A.; Roessner, Veit; Golub, Yulia (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Experiencing traumatic events (TEs), especially interpersonal TEs, is related to an increased risk of developing post-traumatic stress disorder (PTSD). Both TEs and PTSD are associated with a higher risk of substance use and problems in emotion regulation. Little is known about the associations between specific types of TEs, problems with general self-regulation (including cognitive and behavioral components) and substance use severity in adolescents. Knowledge on these associations could provide important approaches for prevention and therapy for adolescents with a history of trauma. Methods This study investigated associations between different types of TEs and PTSD, self-regulation and substance use severity. Moreover, participants were categorized into three groups according to their trauma status: (I) no history of TEs (noTEs), (II) history of TEs but no PTSD diagnosis (TEs), and (III) history of TEs and PTSD diagnosis (PTSD). Differences between the three groups were analyzed in terms of self-regulation and substance use severity. Our sample consisted of N = 89 adolescents aged 12 to 18 years in a child and adolescent psychiatric outpatient clinic in Germany. Substance use severity was only assessed in a smaller subsample (n = 37). Data were obtained from standardized diagnostic procedures and included information on types of TEs and PTSD diagnosis according to ICD-10, problems in self-regulation assessed with the Child Behavior Checklist (CBCL)/ Youth Self Report (YSR) Dysregulation Profile (DP), and substance use severity measured with the Drug Use Disorders Identification Test (DUDIT). Results We found that interpersonal TEs were significantly associated with higher rates of PTSD diagnosis compared to non-interpersonal TEs. We found no significant associations between different types of TEs and both problems in self-regulation and substance use severity. Moreover, our findings do not indicate differences in both self-regulation and substance use severity between trauma statuses (noTEs, TEs, PTSD). Discussion Future studies should consider other characteristics of TEs such as timing and duration when investigating associations with self-regulation. Longitudinal studies are needed to investigate developmental pathways, as a better understanding of the role of characteristics of TEs and self-regulation in the development of PTSD and substance use problems would provide opportunities for prevention and therapy for trauma-exposed patients.